10 Networking Papers: Elegance and Insight - Padmanabhan, Venkat (ACM Computer Communication Review, 2008)
When Jim Kurose invited me to write a piece for the “recommended reading” series in CCR, I thought it would be a fun exercise and accepted the invitation right away. Little did I realize how challenging it would be to put together this list, as much because I was only allowed to pick 10 papers as because I had to steer clear of the many ﬁne papers that had already been picked in previous lists. It has nevertheless been an enjoyable experience and I thank Jim for providing me with this opportunity. I also thank him, Zahir Koradia, and Ram Ramjee for their comments on this article. Rather than focusing on a single topic, I decided to pick papers from across sub-areas of networking that have left a lasting impression on me (and quite possibly on other researchers as well) because of their elegance, the insights they provide, and in many cases both of these. I hope many readers will enjoy reading these papers, if they have not already done so.
Invited paper in the Recommended Reading Series